PENGARUH LITERASI KEUANGAN, TECHNOLOGY ACCEPTANCE MODEL, DAN PERSEPSI RISIKO DALAM PENGGUNAAN QRIS PADA UMKM DI KECAMATAN LIMA PULUH - Hermanto Winata, Willy; Hendy, Hendy; Br Simamora, Rusdiana (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This study aims to analyze the influence of financial literacy, the Technology Acceptance Model (TAM), and risk perception on the use of the Quick Response Code Indonesian Standard (QRIS) among Micro, Small, and Medium Enterprises (MSMEs) in Lima Puluh District. This research is motivated by the increasing digital transformation in non-cash payment systems; however, the adoption rate remains uneven, particularly in semi-urban areas. The method used is a quantitative approach with multiple linear regression analysis. Data were collected through questionnaires distributed to 96 MSME respondents using purposive sampling techniques and analyzed using SPSS through validity tests, reliability tests, classical assumption tests, and hypothesis testing. The results show that partially, the Technology Acceptance Model (TAM) has a positive and significant effect on QRIS usage, while financial literacy has a positive but insignificant effect, and risk perception does not have a significant effect. Simultaneously, all variables have a significant effect, with a coefficient of determination of 62.3%. These findings indicate that perceived ease of use and perceived usefulness are the main factors driving QRIS adoption. Therefore, efforts to increase QRIS usage should focus on enhancing ease of use, perceived benefits, and user experience within the digital payment ecosystem.